Vulvovaginal discharge in pregnancy - Simões, José A.; Giraldo, Paulo C. (Brazilian Journal of Sexually Transmitted Diseases, 1998)
Vaginal díscharge during pregnancy can serve as an important marker of sexually transmitted diseases which in a last analysis could be ünked to results wbich are very unfavorable and barmful to maternal-fetal well-being. On t he otber hand the presence of vaginal discharge during this period, would not necessarily have to be linked to an infectious process which forces the obstetrician to be cautious, allowing no room for error.